KEPEMIMPINAN DI ERA DEMOKRASI DELIBERATIF - Muhammad In'am Esha (lp2m-uin malang, 2013)
This paper discusses the renewal of classical leadership styles in the era of deliberative democracy. In the era of deliberative democracy is no possibility for the emergence of the classical model of leadership. Legitimacy in deliberative democracy lies not in the fact that the majority of vote that has been achieved, but on the ways achieve a fair and equitable manner. Law must be product by fairness and equitable process. The fairness can be processed by public discursive. It will have a powerfull law in the modern community or citizens. In the context of the classical model of this kind of leadership both in the form of a great man theory, trait theory, and the theory of charismatic needed to oversee such a deliberative democracy. Under conditions of deliberative democracy requires great people who are able to have an insight into future developments in line with the new situation of community. We need a leader who concern to devote his intellectual and performance to develop a deliberative democracy.Keyterm: leardership, deliberative, and reactualization